Evaluación del sistema de control interno en la Cooperativa de Ahorro y Crédito "Kulliki Wasi Ltda", en el periodo 2016. - Espín Acosta, Dalila Alexandra (2017)
The research project was developed at the Cooperativa de Ahorro y Crédito Kullki Wasi Ltda., Starting from the breach of current management tools that causes inefficiency in the controls. The project aims to evaluate the internal control system and to know if it is being applied according to the needs of the cooperative, the disadvantages that are occurring within the application in each area of the cooperative and, in turn, to increase the knowledge regarding the theme. The methodology used for the elaboration of this text is based on the bibliographical review, on the systematic and reflexive analysis of secondary sources, related to the field research that consists in the collection of data without manipulating or controlling any variable, using the technique of the observation and the survey applied to the administrative staff, which was indispensable to estimate the subject of study, the internal control questionnaire that will evaluate the cooperative's processes, identifying weak points and proposing control activities or corrective actions. The results through the evaluation of the internal control will minimize the risk and increase the degree of security in the achievement of objectives in relation to the efficiency and effectiveness of operations in turn the reliability of administrative information to compliance with laws and standards applied. As the research will have an impact within the cooperative because it extends the level of confidence in potential investors and thereby the injection of capital, which will directly benefit the sector of the cooperative.